Efektivitas Positive Self-Talk terhadap Penurunan Tingkat Kecemasan dan Depresi pada Lansia dengan Hipertensi di Desa Gulon, Magelang : Penelitian - Qoonit Adzdzaakiya Khairunnisa; Ryka Widyaningtyas; Sri Padma Sari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Elderly individuals with hypertension are vulnerable to psychological disorders, particularly depression and anxiety, which often go undetected—especially in rural areas with limited access to mental health services, such as Lengkongsari, Gulon. This study examined the impact of positive self-talk therapy on reducing anxiety and depression symptoms in three elderly women with hypertension and comorbid physical conditions. A pre-experimental one-group pretest-posttest design was used, with five home visits delivering the intervention. Positive self-talk consists of affirmations and constructive internal dialogue aimed at fostering emotional resilience and adaptive behavior. The Patient Health Questionnaire-9 (PHQ-9) and Hamilton Anxiety Rating Scale (HARS) were used to assess symptoms before and after the intervention. Descriptive analysis revealed a decrease in PHQ-9 scores from 7–8 to 4–5 and in HARS scores from 14–17 to 9–12, indicating improvement from mild to non-clinical levels. Participants also reported enhanced emotional regulation and greater self-confidence. These results suggest that positive self-talk therapy holds promise as a simple, home-based psychosocial intervention for reducing mild anxiety and depression in elderly individuals with hypertension living in underserved rural communities. Further research with larger sample sizes is recommended to validate these findings and explore broader applicability.